1996
DOI: 10.1099/13500872-142-5-1201
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a glycogen-branching enzyme gene, glgB, specifically affects the sporulation-associated phase of glycogen accumulation in Streptomyces aureofaciens

Abstract: ~~~In the course of Sfrepfomyces differentiation, glycogen is accumulated in two discrete phases: in substrate hyphae that undergo aerial mycelium formation (phase I), and during septation of aerial hyphae (phase 11). We have disrupted a previously identified gene, g/gB, encoding a putative glycogen-branching enzyme in Streptomyces aureofaciens. Disruption of the gene had no profound effect on sporulation. However, the amount of glycogen-like polysaccharides, compared to wild-type (WT) S-aureofaciens, decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The gene is accordingly termed glgCI. It follows that another glgC gene must be specific for phase II, echoing the situation previously described for glgB genes (8,18). However, the use of glgCI as a probe at low stringency against Southern blots of S. coelicolor genomic DNA has not revealed candidate sequences, suggesting considerable sequence divergence.…”
Section: Vol 179 1997mentioning
confidence: 97%
See 2 more Smart Citations
“…The gene is accordingly termed glgCI. It follows that another glgC gene must be specific for phase II, echoing the situation previously described for glgB genes (8,18). However, the use of glgCI as a probe at low stringency against Southern blots of S. coelicolor genomic DNA has not revealed candidate sequences, suggesting considerable sequence divergence.…”
Section: Vol 179 1997mentioning
confidence: 97%
“…Likewise, the genes for phase I-and phase II-specific branching enzyme isoforms in various Streptomyces spp. appear in some, but not all, cases to have diverged enough to prevent their simultaneous detection with a single glgB probe (8,18). Surprisingly, glgCI is located far from either of the two known glgB genes, whereas, in all other bacteria analyzed, glgC and glgB are very closely linked, forming part of a cluster of all the major glg genes (22).…”
Section: Vol 179 1997mentioning
confidence: 99%
See 1 more Smart Citation
“…At least some of the genes of glycogen synthesis (i.e. glgB and glgC) are duplicated, one copy of each being speci®c for one of the phases of glycogen deposition (Bruton et al 1995;Homerova et al 1996;Martõ n et al 1997). It now appears that there are du- Fig.…”
Section: Duplicated Operons For Storage Carbohydrate Metabolismmentioning
confidence: 98%
“…Two glgB (branching enzyme) genes have been discovered in S. coelicolor, and phenotypic analysis of disruptants showed that each branching enzyme isoform is responsible for glycogen branching in one of the two locations (Bruton et al, 1995). This situation appears to be general among streptomycetes (Bruton et al, 1995;Homerova et al, 1996). Although only one glgC ( ADPglucose pyrophosphorylase) gene has been identified in S. coelicolor, the phenotype of glgC disruptants showed that this gene is responsible only for phase I glycogen synthesis, and that a second glgC gene must also exist (Martin et al, 1997).…”
Section: The Use Of Food Storage Depots In Coloniesmentioning
confidence: 99%